Single-incision laparoscopic cholecystectomy using conventional instruments in situs inversus totalis - Jhobta, Rajinder Singh (BMJ Case Rep, 2018)
Situs inversus totalis is a rare genetic disorder. Single-incision laparoscopic cholecystectomy (SILC) in situs inversus totalis has been reported rarely. SILC has an advantage of being easier than conventional laparoscopic cholecystectomy in addition to better cosmesis and reduced postoperative pain. We report a case of single-incision laparoscopic cholecystectomy done in a young woman with situs inversus totalis using conventional laparoscopic instruments.